Circadian Intervention Improves Parkinson’s Disease and May Slow Disease Progression: A Ten Year Retrospective Study - Gregory Willis; Takuyuki Endo; Murray Waldman (Brain Sciences)
Background: The involvement of the circadian system in the etiology and treatment of Parkinson’s disease (PD) is becoming an increasingly important topic. The prodromal symptoms of PD include insomnia, fatigue, depression and sleep disturbance which herald the onset of the primary symptoms of bradykinesia, tremor and rigidity while robbing patients of their quality of life. Light treatment (LT) has been implemented for modifying circadian function in PD but few studies have examined its use in a protracted term that characterizes PD itself. Methods: The present exploratory study monitors the effect of LT over a 10 year course of PD in the context of ongoing circadian function. Results: Improvement in circadian based symptoms were seen soon after LT commenced and continued for the duration of the study. Improvement in motor function was more subtle and was not distinguishable until 1.2 years after commencing treatment. Improvement in most motor and prodromal symptoms remained in steady state for the duration of the study as long as patients were compliant with daily use. Conclusions: The sequence of improvement in prodromal symptoms and motor function seen here parallels the slow, incremental repair process mimicking the protracted degenerative sequelae of PD that extends over decades. This process also emulates the slow incremental improvement characterizing the reparative course seen with circadian symptoms in other disorders that improve with LT. Recent findings from epidemiological work suggest that early disruption of circadian rhythmicity is associated with increased risk of PD and the present findings are consistent with that hypothesis. It is concluded that intervening in circadian function with LT presents a minimally invasive method that is compatible with internal timing that slows the degenerative process of PD.